Presença de fatores de risco de doenças cardiovasculares e de lesões em praticantes de corrida de rua - Ishida, Jaqueline De Castro [UNESP] (2013)
This study investigated the anthropometric characteristics and the presence of cardiovascular risk factors (Part 1) as well as occurrence of injuries (Part 2) in road runners. Body mass index, blood pressure (BP), abdominal circumference (AC) and incidence of injuries were evaluated in 94 road runners. Among the participants, 38,5% self-reported as hypertensive, but 41,7% from total had altered BP. Among healthy runners, it was found alterations on BP (42%), AC (9.8%) and 6% presented moderated cardiovascular risk. It was observed that 34% already suffered some injuries and 67.7% derived from training and competition. Age, distance of the running and practice of other activities were associated with presence of injury. The results of the present study allow us to conclude that road runners have a physical condition that facilitates the cardiovascular event during the competition and that contributes to the injuries. Thus it suggests that campaigns need to be done in order to make the runner aware about its health condition.